Background risk influences learning but not generalization of predators. (November 2016) - Chivers, Douglas P.; Mitchell, Matthew D.; Lucon-Xiccato, Tyrone; Brown, Grant E.; Ferrari, Maud C.O.
Abstract : The cognitive abilities of prey animals are closely linked to previous experience with predation risk. For instance, under conditions of high background risk, prey often show an enhanced ability to learn the identity of new predators. When prey learn about predators, they often use the information to make decisions about the predatory nature of unknown, but similar, species. This is referred to as generalization of predator recognition. Often, prey show the strongest response to the species they learned, and a reduced response to other species, with the phylogenetic distance between the learned predator and the other species predicting the degree of generalization. Here, we assessed whether generalization of predator recognition by woodfrog tadpoles is influenced by background level of predation risk in the environment. Given that the likelihood of making a recognition mistake (i.e. failing to respond to an unknown species that is a predator) may be greater in a high-risk environment than in a low-risk environment, we predicted that prey in high risk environments may widen their generalization window and respond with the same intensity to the learned predator and novel predators that are closely related. We found strong evidence that background risk influences the intensity of antipredator responses that prey exhibit towards learned trout predators. Moreover, tadpoles generalized their recognition to closely related trout, but the degree of generalization was independent of background risk. Highlights: Background risk is known to influence cognition of prey animals. We investigated how background risk influenced learning and generalization of predators. Background risk enhanced the responses of tadpoles to learned trout predators. Prey generalized recognition of rainbow trout to other trout species but not all fish. Generalization of predator recognition was independent of background risk.